PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA SPBU COCO PLAJU 21.302.04 PALEMBANG - Saudi Berlian; Indah Octaviana; Riri Hanifa (Jurnal Manajemen Bisnis Unbara, 2022)
This study aims to determine; (1) Conditions of the physical working environment at the Coco Plaju gas station 21,302.04 Palembang; (2) Non-physical working conditions at the Coco Plaju gas station 21,302.04 Palembang; (3) and how the influence between physical and non-physical work environment on employee performance at the Coco Plaju gas station 21,302.04 Palembang. This research uses a descriptive method. Collecting data in this study using a questionnaire. The sample in this study amounted to 35 respondents who were all employees of the Coco Plaju gas station 21,302.04 Palembang. Before processing the questionnaire data from 35 respondents, the validity and reliability of the research questionnaire were tested. The data analysis method used in this research is multiple regression analysis. From the results of the analysis, the regression coefficient of the variables obtained is the physical work environment = 0.616 and the non-physical work environment = 0.098. The hypothesis in this study is evidenced by hypothesis testing, where fcount is 178,249 which is greater than ftable 0.000, then with a significant level of 0.000 less than the probability level of alpha 0.05, so that simultaneously the variables of the physical work environment and non-physical work environment have a significant effect on performance. employees at COCO Plaju gas station 21,302.04 Palembang. In the t-count coefficient for the variable physical work environment and non-physical work environment 0.135 and 0.180 which are greater than ttable 0.000 and 0.002 with a probability level of 0.135 and 0.180, respectively, which are smaller than the probability alpha 0.5, so partially the physical work environment variable and the non-physical work environment has a significant effect on the performance of employees at the Coco Plaju Spbu 21,302.04 Palembang. They must continue to pay attention and keep these two factors in very good condition and if possible be improved again.